2016
DOI: 10.1108/rsr-11-2015-0048
|View full text |Cite
|
Sign up to set email alerts
|

Peer reference assistants in a small liberal arts college: case study

Abstract: Purpose The purpose of this study is to demonstrate how to create and sustain a successful mentoring program for reference student assistants in the liberal arts environment. The study delineates student training, program assessment and the impact on reference practice in a way that can be used at other institutions considering implementing a similar initiative. Design/methodology/approach This case study is written by professionals who have been deeply engaged in initiating, running and assessing the progra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Given the scarcity of material relevant to community college libraries, the authors focused on college and university libraries’ programs. Authors from a small, liberal arts college suggest that students are more likely to approach other students at a service desk than they are library staff or librarians (Gonnerman and Johnson, 2016). One author concluded that “… student learning can be enhanced by the informality inherent in peer-to-peer interaction” (Bodemer, 2014).…”
Section: Developing the Pals Programmentioning
confidence: 99%
See 2 more Smart Citations
“…Given the scarcity of material relevant to community college libraries, the authors focused on college and university libraries’ programs. Authors from a small, liberal arts college suggest that students are more likely to approach other students at a service desk than they are library staff or librarians (Gonnerman and Johnson, 2016). One author concluded that “… student learning can be enhanced by the informality inherent in peer-to-peer interaction” (Bodemer, 2014).…”
Section: Developing the Pals Programmentioning
confidence: 99%
“…The authors also noted that “PALS can also explain difficult concepts in ways that are easier for other students to understand, having recently learned the concepts themselves, and avoiding library jargon. They are familiar with the courses their fellow students are taking and understand the context of the questions they are asked in the library.” Further, the PALS will grow personally through their leadership roles, gain “greater awareness of the variety of information available in their disciplines and become better researchers who are more confident in their abilities” (Faix, 2010; Gonnerman and Johnson, 2016). Additionally, they will obtain experiences and skills that will aid them in finding employment after graduation.…”
Section: Developing the Pals Programmentioning
confidence: 99%
See 1 more Smart Citation
“…Coaching and mentoring between student workers with peers, librarians and paraprofessional staff have also shown to be beneficial to the retention, growth and performance of student assistants (Gonnerman and Johnson, 2016; Slagell and Langendorfer, 2003). Hands-on training providing research and reference support to patrons online and face-to-face, such as practicing scenarios, also help students develop communication skills and provide good customer service (Gonnerman and Johnson, 2016; Faix et al. , 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Recommendations for training reference staff, whether students, paraprofessionals, or librarians, consistently endorse continued development, particularly for advances in available and widely used technology (Courtney and Courtney, 2015;Woodard, 2016). Training for student employees often involves shadowing librarians, as well as completing self-guided tutorials (Gonnerman and Johnson, 2016;Manley and Holley, 2014). Faix (2014) describes a more thorough training process, including ongoing weekly tutorials on the library catalog, subject-specific databases, and reference interview techniques.…”
Section: Literature Reviewmentioning
confidence: 99%